Conceptualizing Globalization (American Journal of Islam and Society, 1998)
The term globe in the English language enjoys the same meaning asthe English word world. The term globalization is now used to denote atrend in world affairs in which several factors and forces impact on theway we view ourselves, our world, societies, cultures, the physical world,and the rest of the universe. The Arabic word for this geographic world is‘ciZum; hence, the Qur’anic usage describing the Creator as Rabb uZ‘&zmSn (The Lord of the Worlds). This Islamic term conjures up animage that cuts across the vast range of beings and their domains of existencein creation.The understanding of globalization that is beginning to gain acceptancethroughout the world centers on the hegemony of the mass mediain the realm of human consciousness. To put the matter humorously, onecan say that the electron has now become the secret mediator betweenpeople located in one part of the world and their counterparts located elsewhereon the globe. It was this image that led the late Marshall MacLuhanto use the metaphor of the tele-village to describe what he believed washappening in the area of human communications.Globalization now manifests itself in five important ways. The firstinvolves the shortening of geographic distances and the ease of humantravel via faster means of locomotion, such as supersonic planes, nuclear-powered ships, high-speed cars, and bullet trains. These modem meansof travel have combined to create a new world order for humanity. Theworld is no longer a wild place where humans must battle with other zoologicalrivals; rather, it has become a place where human creativity andpower now reign supreme, if matters are seen through the eyes of nonhumanflora and fauna.The second manner in which globalization is shaping our world is inthe traversing of physical distances through the effective manipulation ofthe electron in the service of humanity. By virtue of humanity’s scientific ...